“Everyday Ethics” in the care of Hospitalized Older Adults - Seaman, Jennifer B. (Orthop Nurs, 2013)
As the US population ages, the proportion of hospitalized patients over 65 years will continue to increase with a significant number likely to have some degree of cognitive impairment. Because of the high rate of falls-related traumatic injury among older adults, many will require orthopedic services. These patients may have multiple comorbidities and are at increased risk for complications. Varying degrees of cognitive impairment in combination with possible post-operative complications including delirium places these patients at risk for decreased decisional capacity and can create ethical dilemmas during the provision of bedside care. This article explores some everyday ethical dilemmas that nurses face in their care of hospitalized older adults and offers nurses strategies to preserve patient dignity and self-determination while providing high quality, evidence-based nursing care.